2010
DOI: 10.5572/ajae.2010.4.3.150
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ensemble Approach for O3 and PM2.5 Simulation

Abstract: Inter-comparison of chemical transport models (CTMs) was conducted among four modeling research groups. Model performance of the ensemble approach to O 3 and PM 2.5 simulation was evaluated by using observational data with a time resolution of 1 or 6 hours at four sites in the Kanto area, Japan, in summer 2007. All groups applied the Community Multiscale Air Quality model. The ensemble average of the four CTMs reproduced well the temporal variation of O 3 (r= =0.65-0.85) and the daily maximum O 3 concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Hayami et al (2008) were well reproduced in summer in this study, and these results are similar to the results of a study by Morino et al (2010a), in which the ensemble means of four CTMs in the TMA in summer 2007 reproduced observed concentrations (Morino et al, 2010a).…”
Section: Comparison Of Model Performance With That Of Other Modelssupporting
confidence: 90%
See 2 more Smart Citations
“…Hayami et al (2008) were well reproduced in summer in this study, and these results are similar to the results of a study by Morino et al (2010a), in which the ensemble means of four CTMs in the TMA in summer 2007 reproduced observed concentrations (Morino et al, 2010a).…”
Section: Comparison Of Model Performance With That Of Other Modelssupporting
confidence: 90%
“…In general, the performance of CTMs depends strongly on the region and the season, so models must be evaluated for specific target areas and time periods. In Japan, several studies have evaluated PM 2.5 models (Morino et al, 2010a;Ikeda et al, 2014;Shimadera et al, 2014a). However, in those studies, the temporal and spatial coverage of measured PM 2.5 chemical compositions was limited, and thus the performance of the models with regard to PM 2.5 chemical composition was not sufficiently evaluated over the whole of Japan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morino et al (2010b) also indicated that the ensemble average of the four models was effective for evaluating ozone and inorganic aerosol components. One of the issues found in their studies was that the four models used different domains, meteorological fields, boundary concentrations, and emission datasets, which made it difficult to identify the causes of the differences observed among the modeling results.…”
Section: Introductionmentioning
confidence: 94%
“…6 of Shimadera et al, 2013) and illustrated in Fig. 3 of Morino et al (2010a), whereas the differences in the sulfate concentrations between NICAM-g6str and the observations are somewhat greater on 7 and 8 August at Maebashi where the performance of NICAM-g6str is relatively poor, mainly due to the inade- quate horizontal resolution to reproduce the observed meteorological fields, as shown in Sect. 3.1.…”
Section: Evaluation Of Chemical Speciesmentioning
confidence: 83%